Analisis Pengaruh Pertumbuhan Ekonomi Tingkat Inflasi Dan Tingkat Suku Bunga Terhadap Penyaluran Kredit Pada Bank Pemerintah Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2009-2016 - Yuryska Tomi Sumaryo; M. Agus Salim; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2018)
AbstractABSTRACTANALYSIS OF THE INFLUENCE OF ECONOMIC GROWTH ON INFLATION LEVELS AND INTEREST RATES ON CREDIT DISTRIBUTION AT GOVERNMENT BANKSThe purpose of this study was to determine whether economic growth, inflation rates, and interest rates affect the lending to government banks. The population in this study are Government Banks listed on the Bursa Efek Indonesia (BEI) for the period 2009 to 2016. In the selection of samples, this study uses purposive sampling method, in which as many as 4 Government Banks will be used as samples. The company's financial statements have been published so that the required data is available and can be fulfilled. Testing the data in this study using multiple regression analysis method. Based on the test results, it is known that simultaneously, economic growth, inflation rates, and interest rates have a significant effect on credit channeling at Government Banks. And partially, economic growth and inflation rates have a positive and significant effect on lending to government banks while interest rates have a negative and significant impact on lending to Government Banks listed on the Bursa Efek Indonesia in the period 2009-2016.Keywords: Credit Distribution, Economic Growth, Inflation Rate, and Interest Rate